Consistent, Excess Viral Meningitis Incidence Rates in Young Males: A Multi-country, Multi-year, Meta-analysis of National Data. The Importance of Sex as a Biological Variable. (October 2019) - Peer, Victoria; Schwartz, Naama; Green, Manfred S.
Abstract: Background: Sex can be an important biological variable in the immune response to infections and the response to vaccines. The magnitude and consistency in age-specific sex differences in the incidence of viral infections remain unclear. Methods: We obtained data from national official agencies on cases of viral meningitis by sex and age group over a period of 6–16 years from five countries: Canada, Czech Republic, Germany, Israel, and Poland. Male to female incidence rate ratios (RR) were computed for each year, by country, and age group. For each age group, we used meta-analysis methodology to combine the incidence RRs. Meta-regression was conducted to the estimate the effects of age, country, and time period on the RR. Findings: In the age groups < 1, 1–4, 5–9, 10–14, there were consistently higher incidence rates in males, over countries and time. The pooled incidence RRs (with 95% CI) were 1.38 (1.30–1.47), 1.94 (1.85–2.03), 1.98 (1.88–2.07), and 1.58 (1.47–1.71) respectively. In young and middle-age adults there were no differences with pooled incidence RRs of 1.00 (0.97–1.03), and 0.97 (0.94–1.00), respectively. Sensitivity analysis confirms that the results are stable and robust. Meta-regression showed that almost all the variations in the incidence RRs were contributed by age group. Interpretation: The higher incidence rates from viral meningitis in males under the age of 15 are remarkably consistent across countries and time-periods. These findings emphasize the importance of sex as a biological variable in infectious diseases. This could provide keys to the mechanisms of infection and lead to more personalized treatment and vaccine doses and schedules. Funding: There was no funding source for this article.